Primary Hydatid Cyst of Kidney - Ahmed, SS; Islam, SMJ; Baqui, MN; Huda, M; Ali, SM (Journal of Armed Forces Medical College, Bangladesh, 2011)
DOI: http://dx.doi.org/10.3329/jafmc.v7i1.8626 JAFMC Bangladesh. Vol 7, No 1 (June) 2011; 41-42